Implementation Strategy for Village Development Through Information and Communication Technology (ICT) Education in Lame Village - Sri Prasetyo Widodo; Edison Hatoguan Manurung; Sitti Wardiningsih; Bambang Rismadi; Dhea Jessica Lonteng; Eka Putri Sari; Michael Daniel Simanjuntak; Kiki H H Karatahi; Wahyu Ardian; Alwi Sugeng Perdana (Indonesian Journal of Advanced Social Works, 2022)
The presence of the internet and technology can now be utilized as a means of human development, one of which is village development. With the use of information and communication technology, existing obstacles such as knowledge distribution barriers, community participation barriers, and socio-economic barriers can be overcome. This study aims to answer how the strategy for implementing village development through ICT education in Kampung Lame. This research is included in the qualitative research with the case study method. The result of implementing the strategy is that the community is able to recognize and operate the application so that it can be used as a support in carrying out business administration and product design. However, in carrying out these strategies there are challenges, namely the facilities and infrastructure of the village are inadequate so that the human resources in Lame Village are still many who are unfamiliar with technology.